è§†å¬æ³•æ•™å¦å¯¹å¬è¯´æŠ€èƒ½çš„å½±å“åˆ†æž - Pangestika, Jian; Ina, Ina; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIn order to understand the impact on the efficiency of classroom teaching and student interest in learning Chinese using Audiovisual method, the writer collected the literature research paper and the relevant theory of Audiovisual method , the object of test methods for the study is the Student of Sungai Raya High School number 4 conducted pretest, post test and a survey . Writerâ€™s findings are : after the written test and practice, their total score of the post Â test has passing rates and their average score increase. Its indicating that Audiovisual method is able to improve the efficiency of Chinese classroom teaching ; students prefer Audiovisual teaching , the students realise that the teaching method is very interesting and can also improved their own capability of Chinese language. After using Audiovisual teaching method, theÂ studentsâ€™ love for Chinese language rose from Â 75% in the pretest to 90 % in the post test. Therefore, the writer proved that Audiovisual method can improve student's interest in learning Chinese languages .The writer hopes through this research can provide reference for the relevant teaching methods.Â Keywords : Audiovisual Method, Study Interest, Listening and Speaking Skill